N-DEACETYLATION OF SOME AROMATIC AMIDES (Proceedings of the YSU B: Chemical and Biological Sciences, 2019)
N-deacetylation of the amide groups of 4,4'-diamino-N-acetyldiphenylamine, 4,4'-di(p-acetaminoanilino)-N-acetyldiphenylamine and 4,4'-dinitro-N-acetyldiphenylamine were carried out. Reactions were proceeded under reflux, correspondingly by 4N alkaline mixture of methanol / dioxane and concentrated hydrochloric acid. The structures of obtained compounds were confirmed by NMR spectroscopy.
Keywords: 4,4'-diaminodiphenylamine hydrochloride, 4,4'-di(p-aminoanilino) diphenylamine, 4,4'-dinitro-$N$-acetyldiphenylamine, $N$-deacetylation, oligomer